(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2020)
Because of the incorporation of Reinaldo Rojas as member of Academia Nacional de la Historia de Venezuela and how this social scientist promotes the study category Region Barquisimeto, this work reviews evolution of concepts like historical region and geohistory in order to add them to others associated to farming, specially cattle raising, with the purpose of to promote a new category called Historical Livestocking Region Barquisimeto because we understand, and hold, that those things that basically characterizes to Barquisimeto Region is precisely consequence of his agricultural origin.